ADHD in children: a path to free medicines. (February 2016) - Hayden, J.; Flood, M.; McNicholas, F.
Abstract Background Recent media coverage has highlighted discrepancies in the entitlements of children to free ADHD medication across the country. The Department of Health has since ruled that children with ADHD under 16 are entitled to receive free medications. Aims This study examines the cost to the State of ADHD medication and implications for universal coverage under the long-term illness (LTI) scheme for under 16s. We estimate a potential cost for universal coverage for under 16s. Methods Drug reimbursement entitlements were explored for children with ADHD. Data were retrieved from the Primary Care Reimbursement Services for the Community Drug Schemes for 2011. The cumulative and percentage-spent on the LTI scheme was calculated. Results €107, 894 (4.4 %) of the €2.4 million State spent on ADHD medicines was under the LTI scheme in 2011. We estimate a potential cost of €8.4 million for costs of ADHD medicines for the state based on current prescribing patterns. Conclusions There appears to be a significant underutilisation of the LTI scheme affording children free ADHD medication. Public and professional awareness campaigns are required to ensure families get the benefits to which they are entitled, and cost does not become a barrier to treatment adherence and improved outcomes. Leading from this, we propose suggestions for cost-effective prescribing to minimise potential cost implications.